A STUDY OF THE RELATIONSHIP BETWEEN TEACHERS’ PERCEPTION TOWARDS THE PRINCIPAL’S TRANSFORMATIONAL LEADERSHIP STYLE AND TEACHER RETENTION AT BAOJI JINTAI SENIOR MIDDLE SCHOOL, SHAANXI PROVINCE, CHINA - Xuelin (Scholar: Human Sciences, 2022)
This study mainly aimed to determine the relationship between teachers’ perception of the principal’s transformational leadership style and teacher retention by investigating the 193 full-time teachers in the academic year of 2019 (September) – 2020 (January) at the target school. The Multifactor Transformational Leadership Questionnaire (MTLQ) and teacher retention questionnaire based on Maslow’s Hierarchy of Needs was applied to do the survey. Data were analyzed by Mean and Standard Deviation and the Pearson product-moment correlation coefficient. This study demonstrated a positive significant relationship between teachers’ perception of the principal’s transformational leadership style and teacher retention at Baoji Jintai Senior Middle School, Shaanxi Province, China.